Functional degradation and asymmetric network effects - Csorba, Gergely; Hahn, Jong-Hee (The Journal of industrial economics, 2006)
In markets subject to network effects, firms often remove some functions of their original products and sell a functionally-downgraded version at a lower or zero price. This paper aims to provide a pure network effect based explanation of such a practice. Building a functional degradation model with asymmetric network effects, we investigate when and why firms have incentives to introduce a functionally-degraded good and discuss its welfare implication. Reprinted by permission of Blackwell Publishers